Skip to content

Całki podwójne

Oblicz podane całki po prostokącie :

a) \iint\limits_{R}\frac{1}{(x+y+1)^{3}}dxdy gdzie R=[0,1]\times [0,2]

\iint\limits_{R}\frac{1}{(+y+1)^{3}}dxdy=\int\limits_{0}^{1}dx \int\limits_{0}^{2}\frac{1}{(x+y+1)^{3}}dy

\int\frac{1}{(x+y+1)^{3}}dy

x+y+1=t

dy=dt

\int\frac{1}{(x+y+1)^{3}}dy=\int\frac{1}{t^{3}}dt=-\frac{1}{2t^{2}}+C=-\frac{1}{2(x+y+1)^{2}}

\iint\limits_{R}\frac{1}{(+y+1)^{3}}dxdy=\int\limits_{0}^{1}dx \int\limits_{0}^{2}\frac{1}{(x+y+1)^{3}}dy=\int\limits_{0}^{1}[-\frac{1}{2(x+y+1)^{2}}]_{0}^{2}dx=\int\limits_{0}^{1}(-\frac{1}{2(x+3)^{2}}+\frac{1}{2(x+1)^{2}})dx=-\frac{1}{2}\int\limits_{0}^{1}\frac{1}{(x+3)^{2}}dx+\frac{1}{2}\int\limits_{0}^{1}\frac{1}{(x+1)^{2}}dx

x+3=t                    x+1=w

dx=dt                       dx=dw

x=0 \rightarrow t=3                x=0 \rightarrow w=1

x=1\rightarrow t=4                x=0 \rightarrow w=2

-\frac{1}{2}\int\limits_{3}^{4}\frac{1}{t^{2}}dt+\frac{1}{2}\int\limits_{1}^{2}\frac{1}{w^{2}}dw=-\frac{1}{2}[-\frac{1}{t}]_{3}^{4}+\frac{1}{2}[-\frac{1}{w}]_{1}^{2}=-\frac{1}{2}[-\frac{1}{4}+\frac{1}{3}]+\frac{1}{2}[-\frac{1}{2}+1]=-\frac{1}{24}+\frac{1}{4}=\frac{5}{24}

b) \iint\limits_{R}x\cdot \sin(xy)dxdy gdzie R=[0,1]\times [\pi,2\pi]

\iint\limits_{R}x\cdot \sin(xy)dxdy=\int\limits_{0}^{1}dx \int\limits_{\pi}^{2\pi}xsin(xy)dy=\int\limits_{0}^{1}xdx \int\limits_{\pi}^{2\pi}sin(xy)dy=\int\limits_{0}^{1}x[-\frac{1}{x}cos(xy)]_{\pi}^{2\pi}dx=\int\limits_{0}^{1}[-cos(xy)]_{\pi}^{2\pi}dx=-\int\limits_{0}^{1}[cos(xy)]_{\pi}^{2\pi}dx=-\int\limits_{0}^{1}(cos(2\pi x)-cos(\pi x))dx=-\int\limits_{0}^{1}cos(2\pi x)dx+\int\limits_{0}^{1}cos(\pi x)dx=-[\frac{1}{\pi}sin(\pi x)]_{0}^{1}+[\frac{1}{2\pi} sin(2\pi x)]_{0}^{1}=

-\frac{1}{\pi}[sin(\pi)-sin(0)]+\frac{1}{2\pi}[sin(2\pi)-sin(0)]=0

c)\iint\limits_{R}e^{2x-y}dxdy gdzie R=[0,1]\times [-1,0]

\iint\limits_{R}e^{2x-y}dxdy=\int\limits_{0}^{1}dx \int\limits_{-1}^{0}e^{2x-y}dy=\int\limits_{0}^{1}-[e^{2x-y}]_{-1}^{0}dx=\int\limits_{0}^{1}-(e^{2x}-e^{2x+1})dx=-\int\limits_{0}^{1}e^{2x}dx+\int\limits_{0}^{1}e^{2x+1}dx

2x=t                  2x+1=w

dx=\frac{1}{2}dt            dx=\frac{1}{2}dw

x=0 \rightarrow t=0        x=0 \rightarrow w=1

x=1 \rightarrow t=2         x=1 \rightarrow w=3

-\int\limits_{0}^{2}e^{t}\frac{1}{2}dt+\int\limits_{1}^{3}e^{w}\frac{1}{2}dw=-\frac{1}{2}\int\limits_{0}^{2}e^{t}dt+\frac{1}{2}\int\limits_{1}^{3}e^{w}dw=-\frac{1}{2}[e^{t}]_{0}^{2}+\frac{1}{2}[e^{w}]_{1}^{3}=-\frac{1}{2}(e^{2}-1)+\frac{1}{2}(e^{3}-e)=\frac{1}{2}(e^{3}-e^{2}-e+1)